Mediametrics technologies - Madina Nuriddinova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Тhis article discusses mediametry technologies, their types and application procedure. The study of the media through mediametric technologies and the promotion of their activities